Foliar nutrient contents and yield performance of blackberry with potassium fertilization - Gaurat, Jéssica Oliveira; Cruz, Maria do Céu Monteiro da; Lima, João Esdras; Sena, Cintia Gonçalves; Santos, Núbia Cassiana; Silva, Enilson de Barros (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the yield performance and foliar nutrient contents of blackberry (Rubus sp.) cultivars in response to the increase in potassium fertilization. The experiment was carried out in a soil with pH 5.2 and 22 mg dm-3 K content in the fourth and fifth years of production of the Brazos, Guarani, BRS Tupy, and BRS Xavante cultivars, grown in the state of Minas Gerais, Brazil. The tested K2O rates were distributed in a 4x4 factorial arrangement, which consisted of four rates of K2O per plant (10, 20, 30, and 40 g) and of the four blackberry cultivars, distributed in four randomized complete block designs. The maximum economic efficiency (MEE) yield, the formation of primocanes, and the critical level of foliar nutrients were evaluated. The K fertilization recommended for blackberry cultivation in Brazilian conditions is not sufficient to maintain foliar nutrient contents at an adequate level. Fertilization with 20 g per plant per year of K2O, twice the recommended amount, favors the MEE yield, compatible with the yield performance of the cultivars. Foliar nutrient contents should be evaluated to recommend the proper fertilization for the orchard to reach its maximum yield potential.